State marine policy regulation: risk management aspects - I. M. Nyenno (Ринкова економіка: сучасна теорія і практика управління)
The article deals with the risks of implementing the state maritime policy. Causes and factors of their occurrence, consequences and indicators of risks'monitoring are consistently presented. Particular attention is paid to the human resource risk. Based on a comparative analysis of privatized and state port administrations, the main distinctive features of this risk’s emergence have been identified. It is determined that the profitability orientation is inherent to the state port administrations to a lesser extent.